2017
DOI: 10.4103/2212-5531.201889
|View full text |Cite
|
Sign up to set email alerts
|

A survey on undiagnosed active pulmonary tuberculosis among pregnant mothers in mekelle and surrounding Districts in Tigray, Ethiopia

Abstract: Objective/BackgroundTo determine the prevalence of undiagnosed active pulmonary tuberculosis (PTB) cases and sensitivity, specificity, and positive and negative predictive values of symptom combinations for undiagnosed TB infection in human immunodeficiency virus (HIV)-positive and HIV-negative pregnant mothers attending antenatal care (ANC) clinics. Mycobacterium TB and HIV are the leading causes of death among women of reproductive age worldwide. Symptom screening is the final step in the World Health Organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
1
7
0
1
Order By: Relevance
“…First, the yield of TB was abysmally low (0.02%) and a whopping 4203 women had to be screened to find one case of TB. This is one of the lowest yields of TB reported among pregnant women, barring a study from Ethiopia which reported a yield of 0.01% [21]. In contrast, the yield of TB varied from 0.1% to 1.6% in previous studies from Kenya, South Africa, Tanzania, Zambia and India [10,13,[21][22][23].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…First, the yield of TB was abysmally low (0.02%) and a whopping 4203 women had to be screened to find one case of TB. This is one of the lowest yields of TB reported among pregnant women, barring a study from Ethiopia which reported a yield of 0.01% [21]. In contrast, the yield of TB varied from 0.1% to 1.6% in previous studies from Kenya, South Africa, Tanzania, Zambia and India [10,13,[21][22][23].…”
Section: Discussionmentioning
confidence: 69%
“…This is one of the lowest yields of TB reported among pregnant women, barring a study from Ethiopia which reported a yield of 0.01% [21]. In contrast, the yield of TB varied from 0.1% to 1.6% in previous studies from Kenya, South Africa, Tanzania, Zambia and India [10,13,[21][22][23]. The variation in yield might be explained by the differences in study population (whether only HIV-positive or all pregnant women were included), HIV prevalence, definitions of TB used and the background TB prevalence.…”
Section: Discussionmentioning
confidence: 74%
“…As part of our sensitivity analyses, we excluded one large study [28]; estimates of TB-HIV co-infection prevalence did not change.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the I 2 was greater than 75% and hence the summary statistics were made using the random-effects models in which the individual study weight is the sum of the weight used in the fixed effects model and the between-study variability [27]. To analyze the basis of heterogeneity, we performed a sensitivity analysis by excluding one largest study [28] and by analyzing the groups according to the geographic area.…”
Section: Methodsmentioning
confidence: 99%
“…Obviously, TB among pregnant women has public-health importance not only because of the risk of mortality and morbidity to the mothers, but also because it is harmful to the neonates 24 . Therefore, once pregnant women are diagnosed with active TB, action should be taken immediately 8 .…”
Section: Discussionmentioning
confidence: 99%